Supply Chain Management Information System Model for Human Resource Management for Higher Education Institutions in Thailand - Chansamut, Artaphon (International Journal of Supply Chain Management, 2022)
The research aim is to develop supply chain management information system model for human resource management for higher education institution in Thailand which included evaluate supply chain management information system model for human resource management for higher education institution in Thailand The sample group consists of   fifteen experts in arranging information  system, supply chain and professionals,  human resource. All totalling 15 experts. The research instrument was a questionnaire. The data were analysed using arithmetic mean and standard deviation. The model  comprises  5 key components , namely, Suppliers, Processors Manufacturers                           , RetajlersExporters and customers. The overall evaluation result supply chain management information system model for human resource management for higher education institution in Thailand shows the overall rating mean of 3.61 and standard deviation of 0.75, which means that supply chain management information system model for human resource management for higher education institution in Thailand is appropriate at the high level and can be applies in support the tasks.